The Effect of the Implementation of Total Quality Management (TQM) on the Performance of the Distribution Section at PT PLN (Persero) UP3 Mataram - Arif Budiman (International Journal of Economics Business and Social Sciences, 2026)
This research is motivated by the importance of improving the quality of service and reliability of electricity distribution at PT PLN (Persero) UP3 Mataram in the midst of increasing public demands for effective, efficient, and customer satisfaction-oriented public services. Total Quality Management (TQM) is one of the management approaches that is considered to be able to improve the quality of organizational performance through continuous improvement, customer focus, employee involvement, and overall quality control. This study aims to analyze the effect of the implementation of TQM on the performance of the distribution department at PT PLN (Persero) UP3 Mataram and to find out the extent to which the implementation of TQM is able to improve the quality of electricity distribution services. The implementation of TQM affects the achievement of distribution performance indicators and service effectiveness at PT PLN (Persero) UP3 Mataram which is the main focus of this research question.  A descriptive qualitative approach was applied in this study and data collection techniques were carried out through observation and interview activities as well as documentation and literature studies. The stages of data reduction and data presentation and conclusion drawing are used systematically to conduct data analysis. The positive impact on improving the performance of the distribution section is shown by the results of the research on the implementation of TQM. The decrease in the value of SAIDI from 161.65 to 130.52 minutes/customer and the decrease in the value of SAIFI from 2.06 to 1.79 times/customer as well as the decrease in the value of ENS from 728.22 MWh to 240.82 MWh show clear evidence of the improvement in operational performance. A significant decline was also experienced by negative feedback ratings and repeated complaints of disturbances in the field. Increasing operational effectiveness and the quality of electricity distribution services can be achieved optimally through the application of TQM principles such as continuous improvement and customer focus as well as teamwork and consistent quality control based on these scientific findings. The conclusion of this study shows that the implementation of Total Quality Management (TQM) has a positive effect on improving the performance of the distribution department at PT PLN (Persero) UP3 Mataram. The implementation of TQM not only improves the quality of service and reliability of electricity distribution, but also strengthens customer satisfaction and operational efficiency of the company. This research contributes to the development of quality management and operational management science, especially in the public service and electricity sectors. The next study is recommended to use a quantitative approach or mixed method with a wider coverage of the area and add other variables such as organizational culture, leadership, and digital quality management to obtain more comprehensive result.